Resilience and 'Climatizing' development: Examples and policy implications - Boyd, E.; Osbahr, H.; Ericksen, Polly J.; Tompkins, E.L.; Lemos, M.C.; Miller, F. (Springer, 2008)
There is a growing scientific consensus on climate change and the need for adaptation, yet an impasse on realizing development for the rural and urban poor. Emily Boyd et al. suggest that a resilience lens may assist development policy to consider pathways towards more successful livelihood transformations in the face of climate change. We recognize that there are also limitations to this approach.